The Converging Technology Revolution and Human Capital : Potential and Implications for South Asia - Bashir, Sajitha (Washington, DC: World Bank, 2021)
South Asia is heavily impacted by the devastating loss of lives and human capital from the COVID-19 pandemic and the converging technology revolution sweeping the globe. The Converging Technology Revolution and Human Capital: Potential and Implications for South Asia looks at how the region could capitalize on these technologies to accelerate its development of human capital and promote adaptability and resilience to future shocks. The convergence of technological breakthroughs spanning biotechnology, nanotechnology, information technology, and cognitive science is driven by artificial intelligence, data flows, computing power, and connectivity. These breakthroughs can improve service delivery, productivity, and innovation, but they can also exacerbate inequalities and eliminate people’s agency and empowerment. This report analyzes these trends in the region, offering a comprehensive agenda to exploit the opportunities offered by converging technologies while minimizing the risks to vulnerable populations. It proposes strategies for building public sector capacity and promoting data and technology governance frameworks in a rapidly evolving technology landscape.